An evaluation of the joint BPS-PACD functional literacy project - Cordeta, Remedios (Santos) 1921- (1960)
This study determined how well the objectives set forth in the Memorandum of Understanding Agreement are being met and to know precisely the results produced in five barrios of San Miguel, Bulacan after a period of more than two years.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Education of adults; Community development -- Philippines -- San Miguel (Bulacan).